The Effect of Variations in Disc Diameter on Frictional Moment, Distance and Braking Time on Three-Wheeled Motorcycles for Agricultural Transportation - Triadji Nugroho, Wendy; Hidayat, Roman; Subagja, Hariadi (Politeknik Negeri Jember, 2025)
This study aimed to evaluate the effect of disc diameter variation on friction moment, braking distance, and braking time on three-wheeled motorcycles for agricultural transportation. It involved testing three variations in disc size: 220, 260 and 300 mm, with three speed variations: 20, 30 and 40 km/h. The testing results revealed that the larger the disc diameter, the greater the friction moment. The 300 mm disc yielded the highest friction moment of 7246.1 N.m. The shortest braking distance (9.5 m) was achieved by the 300 mm disc at a speed of 20 km/h. For a speed level of 30 and 40 km/h, the braking distances were 18.20 and 27.2 m. Braking times also showed a similar pattern, where the 300 mm disc brake had the shortest braking time of 3.63 seconds at a speed of 20 km/h. At speed levels of 30 km/h and 40 km/h, braking times were 5.52 and 6.35 seconds. The test data showed that disc brakes with a larger diameter increased braking power by shortening the braking distance and time while increasing the friction moment, indicating that the disc brake size has a significant effect on the braking performance of three-wheeled motorcycles used for agricultural transportation the disc brake size has a significant effect on the braking performance of three-wheeled vehicle used for agricultural transportation.